Cynomys summer: a photojournalistic reflection and data analysis of an ongoing prairie dog plague study - Ewing, Matthew, author (Colorado State University. Libraries, 2024)
In my thesis, I provide a photojournalistic account of my experiences working on a research project. The project is working to better understand genetic resistance to the plague (Yersinia pestis) in Black-tailed prairie dogs (Cynomys ludovicianus). Throughout the summer, I used my photography skills to photograph the various species that rely on the prairie dogs and document aspects of our research. I showcase these photos in my thesis, while providing research based context to prairie dog ecology and our research. I also analyzed prairie dog growth rates in juveniles between sexes, and found no significant differences between males and females.
Colorado State University - University Honors Program.
StoryMap link (intended viewing format): https://arcg.is/j50Sj.
Keywords: photojournalism; photography; prairie dog; plague